High fat diet partially attenuates fermentation responses in rats fed resistant starch from high‐amylose maize - Charrier, Jason A.; Martin, Roy J.; McCutcheon, Kathleen L.; Raggio, Anne M.; Goldsmith, Felicia; Goita, M'Famara; Senevirathne, Reshani N.; Brown, Ian L; Pelkman, Christine; Zhou, June; Finley, John; Durham, Holiday A.; et al. (Obesity (Silver Spring, Md.), 2013)
Objective The effects of type 2 resistant starch from high‐amylose maize (HAM‐RS2) in rodents fed with low‐fat diets were demonstrated in previous studies. Fish oil is also reported to reduce body fat. In the current study, the effects of high fat and fish oil on HAM‐RS2 feeding in rats were investigated. Design and Methods Rats were fed 0 or 27% (weight) HAM‐RS2 with low (15% energy) or high fat (42% energy) diets that included 0 or 10% (energy) tuna oil to test the effect of HAM‐RS2 in diet‐induced obesity and effects of tuna oil. Data were analyzed as 2 × 2 × 2 factorial. Results Rats fed HAM‐RS2 had decreased cecal contents pH, increased cecal and cecal contents weight, increased cecal contents acetate, propionate, and butyrate, increased GLP‐1 and PYY, and decreased abdominal fat. However, high fat partially attenuated effects of HAM‐RS2, but increased GLP‐1 active. Dietary tuna oil had limited effects at concentration used. Conclusions Results demonstrated that a high fat diet partially attenuates the response to HAM‐RS2. The mechanism may center on reduced levels of cecal contents propionate and butyrate and reduced serum PYY. This study demonstrated that with consumption of high fat, HAM‐RS2 produces fermentation but results in partial attenuation of effects.